Exploring Relationship Value through Second-Order Model and Importance-Performance Map - Prasetya, Prita; Najib, Mukhamad; Darmawan, Teuku Fajar Akbar (MIX: JURNAL ILMIAH MANAJEMEN, 2025)
Objectives: This research aims to examine the direct impact of relationship value (RV) on distributor satisfaction through a second-order analysis using structural equation modeling (SEM). The study focuses on understanding how various dimensions of RV contribute to enhancing satisfaction among distributors.Methodology: A cross-sectional survey was conducted, collecting data from 193 middle-class distributors. The analysis employs a second-order model to explore the relationships between RV dimensions and distributor satisfaction, while also utilizing Importance-Performance Map Analysis (IPMA) to identify key areas for improvement.Finding: The results confirm the direct influence of RV on distributor satisfaction. The second-order model effectively identifies several critical dimensions of RV that significantly enhance satisfaction. IPMA results highlight that strengthening distributor reliance on sellers by providing more valuable market insights can boost satisfaction. Additionally, RV supported by seller expertise and timely market entry can foster stronger relationships with principals.Conclusion: This study offers valuable insights for managers, recommending a focus on the most critical dimensions of RV to improve distributor satisfaction and overall performance. By enhancing support and expertise, companies can build more positive and lasting relationships with their distributors.